Antibody Response After Third Vaccination With mRNA-1273 or BNT162b2: Extension of a Randomized Controlled SARS-CoV-2 Noninferiority Vaccine Trial in Patients With Different Levels of Immunosuppression (COVERALL-2). (30th March 2023) - Griessbach, Alexandra; Chammartin, Frédérique; Abela, Irene A; Amico, Patrizia; Stoeckle, Marcel P; Eichenberger, Anna L; Hasse, Barbara; Braun, Dominique L; Schuurmans, Macé M; Müller, Thomas F; Tamm, Michael; Audigé, Annette; et al.
Abstract: Extension of the COVERALL (COrona VaccinE tRiAL pLatform) randomized trial showed noninferiority in antibody response of the third dose of Moderna mRNA-1273 vaccine (95.3% [95% confidence interval CI, 91.9%–98.7%]) compared to Pfizer-BioNTech BNT162b2 vaccine (98.1% [95% CI, 95.9%–100.0%]) in individuals with different levels of immunosuppression (difference, −2.8% [95% CI, −6.8% to 1.3%]). Abstract : The extension of the COrona VaccinE tRiAL pLatform trial (COVERALL) showed the non-inferiority in antibody response of the third Moderna mRNA-1273 vaccine dose compared to the third Pfizer-BioNTech BNT162b2 vaccine in individuals living with HIV and solid organ transplant recipients.